The art and science of describing nature’s surrealists: Foreword from the Editors - Evangelista, Olivia; Takiya, Daniela Maeda; Dietrich, Christopher H. (Zootaxa, 2017)
This special issue of Zootaxa is published in honor of Dr. Albino Morimasa Sakakibara from the Universidade Federal do Paraná, Brazil, one of the most prolific living taxonomists of auchenorrhynchan Hemiptera. Dr. Sakakibara is the author of more than 100 scientific articles spanning the years 1968 to 2017. His works have encompassed various fields of biology including natural history, comparative morphology, phylogenetics, and taxonomy treating approximately 60 genera of treehoppers, leafhoppers, and spittlebugs. His outstanding record of contributions to our field also includes an extensive and successful history of graduate student training—twelve taxonomists currently working on several insect groups—along with thorough curation of the insect collection at his home institution, now constituting inarguably the most comprehensive holdings of Auchenorrhyncha in Brazil.